Respecting Equality: Practical Manifestations of Intergovernmental Integration Outside the Treaties - Sehnálek, David (Unequal Equals? The Status of Member States in an Integrating European Union, 2026)
In this chapter I will examine the effectiveness of intergovernmental cooperation in the EU through an analysis of subsidiary treaties concluded between Member States. I will focus on the Brussels and Rome Conventions, the Fiscal Compact, Convention on the protection of the European Communities’ financial interests, and the UPC Convention. I will assess their success and impact on the development of the EU, arguing that these intergovernmental agreements, despite being limited in number, represent important milestones of integration and may offer solutions to the shortcomings of the current supranational model of the EU. I will also explore the question of whether and in what areas this approach could be developed further. That is, whether these treaties could be a model for further development of the EU. From the perspective of equality between Member States, it is important that these forms of cooperation do not circumvent cooperation within the EU. In other words, not only is the interest of those states that wish to participate in cooperation important, but the perspective of those states that may not be interested in cooperation should also be considered. From the perspective of equality between Member States, it is essential that these forms of cooperation do not bypass or undermine cooperation within the EU framework. In other words, not only do the interests of the participating states matter, but also the perspectives and concerns of those Member States that choose not to take part, which must be duly considered.